2000
DOI: 10.1038/sj.gene.6363665
|View full text |Cite
|
Sign up to set email alerts
|

Ku autoantigen (DNA helicase) is required for interleukins-13/-4-induction of 15-Lipoxygenase-1 gene expression in human epithelial cells

Abstract: As reported previously in human monocytes, a human lung epithelial cell line, A549, showed de novo induction of 15-Lipoxygenase-1 (15-LO-1) in response to interleukins-13 (IL-13) and −4 (IL-4). In this cell line, 15-LO-1 expression, by RT-PCR and western blotting, was observed following 6 and 24 h of exposure to human IL-13 (ED 50 5 ng/ml) and IL-4 (ED 50 0.2 ng/ml). We have previously shown that no cis-acting regulatory elements exist within the 15-LO-1 promoter region. To define IL-13 and IL-4 responsive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Indeed, the gene expression of 15-LO-1, considered an anti-inflammatory molecule, is known to be regulated by several proinflammatory molecules. 27,28 Consequently, as bladder disease progresses, 15-LO-1 activity is no longer required and thus its expression is concomitantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the gene expression of 15-LO-1, considered an anti-inflammatory molecule, is known to be regulated by several proinflammatory molecules. 27,28 Consequently, as bladder disease progresses, 15-LO-1 activity is no longer required and thus its expression is concomitantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism of poly ADP-ribosylation has been shown to contribute to various cellular processes, including DNA repair [18], transcriptional regulation [19], [20], [21], and cell cycle progression [21]. Ku80 and Ku70 form the heterodimeric DNA binding complex Ku80/70 that associates with PARP-1 and, among other functions, contributes to the regulation of gene transcription [22], [23], [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides its vital role in DNA repair, reports have implicated Ku in certain other cellular processes, including telomere maintenance, antigen receptor gene arrangements, cell cycle regulation, regulation of heat shock-induced responses, and specific gene transcription and apoptosis. For example, it has been shown that Ku is required for interleukin-13/-4-induction of 15-lipoxygenase-1 gene expression in human epithelial cells [28]. Here, Ku is induced in response to IL-13 and IL-4, and a 29 bp region within the -353 to -304 bp region of the 15-LO-1 promoter is required for its binding and subsequent induction of 15-LO-1 gene expression.…”
Section: Resultsmentioning
confidence: 99%